Immunological aspects of host–pathogen crosstalk in the co-pathogenesis of diabetes and latent tuberculosis - Verma, Arpana; Kaur, Maninder; Luthra, Princy; Singh, Lakshyaveer; Aggarwal, Divya; Verma, Indu; Radotra, Bishan D.; Bhadada, Sanjay Kumar; Sharma, Sadhna (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Diabetes is a potent risk factor for the activation of latent tuberculosis and worsens the tuberculosis (TB) treatment outcome. The major reason for mortality and morbidity in diabetic patients is due to their increased susceptibility to TB. Thus, the study was conducted to understand the crosstalk between M. tuberculosis and its host upon latent tuberculosis infection and under hyperglycemic conditions or diabetes. Methods An animal model was employed to study the relationship between latent tuberculosis and diabetes. BCG immunization was done in mice before infection with M. tuberculosis, and latency was confirmed by bacillary load, histopathological changes in the lungs and gene expression of hspX, tgs1, tgs3 and tgs5. Diabetes was then induced by a single high dose of streptozotocin (150 mg/kg body weight). Host factors, like various cytokines and MMPs (Matrix metalloproteinases), which play an important role in the containment of mycobacterial infection were studied in vivo and in vitro. Results A murine model of latent TB was developed, which was confirmed by CFU counts (<104 in the lungs and spleen) and granuloma formation in lungs in the latent TB group. Also, the gene expression of hspX, tgs1, and tgs5 was upregulated, and after diabetes induction, blood glucose levels were >200 mg/dl. An in vitro study employing a THP-1 macrophage model of latent and active tuberculosis under normal and high glucose conditions showed that dormant bacilli were better contained in the presence of 5.5 mM glucose concentration as compared with active bacilli. However, the killing and restriction efficiency of macrophages decreased, and CFU counts increased significantly with an increase in glucose concentration. Discussion The decreased levels of MCP-1, decreased expression of mmp-9, and increased expression of mmp-1 in the latent group at high glucose concentrations could explain the failure of granuloma formation at high glucose conditions.